Adverbs in conceptual semantics - Hofland, S (2011)
The thesis discusses and evaluates semantic representations of predicate-oriented modification (specifically by manner adverbs) and participant-oriented evaluative modification (by so-called “subject-oriented” adverbs). Analyses are proposed within the framework of Conceptual Semantics.